An investigation of social computing - Schlenkrich, Lara (Rhodes University, Faculty of Commerce, Department of Information Systems, 2009)
Social network sites have recently become extremely popular online destinations as they offer users easy ways to build and maintain their relationships with each other. Consequently, students, lecturers, teachers, parents and businesses are using these tools to communicate with each other in a fast and cost-effective manner. However, literature suggests that the full potential of social network sites has not yet been revealed since users are still battling to overcome the various negative characteristics surrounding these sites. A framework for appropriate use of these sites is needed so that users are able to overcome these negative aspects, allowing them to be more effective and use the sites successfully. The goal of this research is to construct a framework for perceived successful use of social computing tools in educational institutions. This framework will include critical success factors that need to be adopted by users in order to develop the positive aspects of social computing, while at the same time overcoming the disadvantages experienced by users. Factors for successful use were derived from the literature and consolidated into a theoretical framework in order to understand the factors that drive successful use of social network sites. Measures used to test successful use of social network sites were also derived from these sources and were included in the same theoretical framework; these measures allow users to evaluate the extent of perceived successful use of social network sites. This framework was tested empirically by means of a pilot study and online survey, and revised according to the results of the survey. The factors were identified using Cronbach alpha coefficients (in the pilot study) and exploratory factor analysis to confirm the reliability of the scales developed. Pearson product-moment correlation coefficient analysis, t-tests and Pearson Chi-Square tests were used to measure the relationships amongst the variables in the framework proposed in this research. The factors influencing perceived successful use of social network sites were identified by the empirical study as: "¢ Privacy and Security Settings need to be enabled. These are split into: - Settings: content that users allow others to see - Viewers: people who are allowed onto a user's profile "¢ It is necessary for users to practise Legal and Acceptable Activities when using social network sites "¢ Suspect Information needs to be checked before sharing it with others "¢ Personal and Professional Time needs to be separated to ensure that work is completed before social activities occur "¢ Users need to practise Professional and Ethical Behaviour "¢ Users need to have a Positive Attitude when using social network sites "¢ Usability of sites affects their success. This includes: - technical capacity (broadband) - ease of use - functionality (range of features and functions) "¢ Current and Controversial Issues need to be discussed on social network sites. The extent to which social network sites are being used successfully can be evaluated by the presence of the following measures: "¢ Range of Content must be available to users. This includes: - Content displayed on profiles - Viewers able to visit profiles "¢ Visitors Behaviour is monitored and no unwanted visitors are present users' profiles "¢ Social Contracts found on sites are followed by users "¢ Critical Thinking Skills and Accurate Information are displayed by users "¢ Work is completed before social activities occur on sites "¢ A Variety of Users is present on sites "¢ Collaboration between people as well as variety of opinions exist on sites "¢ Social Capital (well-being) is present after users have been on sites "¢ Learning and Advising Skills are enhanced on sites. The framework developed provides users with a useful instrument to overcome the negative characteristics associated with social network sites. If used successfully, social network sites can offer lecturers and students a unique method to develop their relationship, creating a positive learning experience.
Keywords: Online social networks; Online social networks -- Law and legislation; Interpersonal communication; Internet in education; Education -- Communication system; Education -- Data processing